2018
DOI: 10.1186/s12199-018-0743-y
|View full text |Cite
|
Sign up to set email alerts
|

Background factors of chemical intolerance and parent–child relationships

Abstract: BackgroundChemical intolerance is a widespread public health problem characterized by symptoms that reportedly result from low-level exposure to chemicals. Although several studies have reported factors related to chemical intolerance in adults, the impact of family members has not been reported. In the present study, we investigated the background factors related to chemical intolerance in family members and parent–child relationships.MethodsWe distributed a self-reported questionnaire to 4325 mothers who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…15 However, no association was observed between employment and chemical intolerance among 2044 Japanese women aged 18-47 years. 35 Moreover, the directionality of the association is not possible Open access establish due to the cross-sectional study designs in our and other studies, and we cannot rule out that employment status can be a consequence of having MCS. From a population-based cohort in Atlanta, Georgia, USA (total n=1291), 1.8% of the individuals with self-reported chemical sensitivity (n=193) reported loss of employment due to their sensitivities.…”
Section: Discussionmentioning
confidence: 68%
“…15 However, no association was observed between employment and chemical intolerance among 2044 Japanese women aged 18-47 years. 35 Moreover, the directionality of the association is not possible Open access establish due to the cross-sectional study designs in our and other studies, and we cannot rule out that employment status can be a consequence of having MCS. From a population-based cohort in Atlanta, Georgia, USA (total n=1291), 1.8% of the individuals with self-reported chemical sensitivity (n=193) reported loss of employment due to their sensitivities.…”
Section: Discussionmentioning
confidence: 68%
“…Three 5-year follow-up studies reported that participants who developed CI between baseline and follow-up reported more health complaints or negative psychosomatic states at baseline compared to participants who did not develop CI [101, 103, 104]. An association of risk of acquiring CI with measures of inherent physical constitution, such as cold sensitivity or the presence of an indoor cat during childhood, has also been reported [105]. In this study, the prevalence of current CI in mothers was 4.5% and in their 3-year-old children was 0.25%, or approximately one eighteenth of that reported by their mothers [105].…”
Section: Methodsmentioning
confidence: 99%
“…An association of risk of acquiring CI with measures of inherent physical constitution, such as cold sensitivity or the presence of an indoor cat during childhood, has also been reported [105]. In this study, the prevalence of current CI in mothers was 4.5% and in their 3-year-old children was 0.25%, or approximately one eighteenth of that reported by their mothers [105]. Devriese et al reported that generalization of acquired somatic symptoms in response to odorous substances especially occurred in individuals with high negative affectivity [89].…”
Section: Methodsmentioning
confidence: 99%
“…Among these, Azuma et al, showed alterations in cerebral flow in MCS patients after exposure to particularly unpleasant compounds. The same author suggested also that inherent physical constitution and childhood housing environment are associated with a risk of acquiring chemical intolerance . Others have instead shown peculiar genetic polymorphisms that can explain the symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] In 80% of patients the predominant symptoms are asthenia, arthromial pain, dyspepsia, coriza, eructation, chest pain, insomnia. 13 IEI/MCS is a widespread public health problem 14 currently considered a special case of chemical intolerance (CI), or a tendency to develop nonspecific symptoms involving multiple systems (eg, nervous, gastrointestinal, ocular) in response to exposure to some specific chemicals. The prevalence of the CI is 33% in the general population, while the MCS has a prevalence between 0.5% and 6%.…”
Section: Introductionmentioning
confidence: 99%